HUBUNGAN LINGKAR KEPALA DENGAN REFLEKS PRIMITIF TERHADAP TUMBUH KEMBANG BAYI USIA 0-6 BULAN DI PUSKESMAS SUDIANG - Darwis Durahim; Fahrul Islam; Sri Saadiyah (Media Fisioterapi Politeknik Kesehatan Makassar, 2020)
The size of a normal baby's head circumference shows normal primitive reflexes. Primitive reflexes are very important and essential in the process of child development. The development of good primitive reflexes will cause the child's growth and development to run smoothly.This type of research is analytic with a cross sectional design. The sample of this study was 46 respondents who were taken based on the incidental method with the aim of knowing the relationship between head circumference and primitive reflexes on the growth and development of infants aged 0-6 months at the Sudiang Health Center. The results of statistical analysis using the chi-square test obtained P=0.001 for the relationship of head circumference to growth and development and P=0.000 for the relationship of primitive reflexes to growth and development. When P<0.05 then H0 is rejected and Ha is accepted. So the result is that there is a relationship between head circumference and primitive reflexes for the growth and development of babies aged 0-6 months.Neurological examination, especially primitive reflexes, is an important thing that must be considered in order to minimize injuries or neurological diseases that will have an impact on delays or even disrupt the growth and development of the baby. While the physical examination, especially the measurement of head circumference, is equally important in order to determine the volume or development of the brain in babies every month. Keywords: Head Circumference, Primitive Reflexes, Growth and Development, Babies